Italo Calvino in Spagna: presenze e assenze di uno scrittore 'altro' - Giordano, Chiara (Incontri. Rivista europea di studi italiani, 2024)
This essay focuses on the fluctuating reception of Italo Calvino in Spain, in the period between 1959, when the Italian writer made his first trip to Majorca, and the present day. The aim of the proposed mapping is to foreground the different faces of a Calvino other than oneself, dwelling on the least analysed moments and on the reasons, including ideological and literary ones, that underlie the articulation of Calvino's authorial profile in the Iberian Peninsula. Specifically, we will examine the translations into Castilian distributed in Spain in the decades following the so-called Ley Fraga and the progressive opening of the Spanish publishing market following the death of General Francisco Franco and the end of the dictatorship.